Synaptic microRNA expression and function in the central nervous system. - Mecker, Samantha. (2017)
Abstract: Regulated gene expression is essential to the ability of cells in the body to perform specialized functions. In 2001, the Human Genome project published an almost complete sequencing of the human genome, and came to the surprising discovery that only 1.5% of it encode proteins while over 90% was believed to be `junk DNA' that is never transcribed. Since then, novel technologies such as microarray profiling have demonstrated that the majority of the non-coding sequence is actively and dynamically transcribed into regulatory RNA sequences. Among the multiple families of non-coding RNA that have been discovered, one of the most important identified thus far is microRNA. The first microRNA (miR) to be described was lin-4 in the model organism Caenorhabditis elegans (C. elegans) in 1993, and since then hundreds of miRs have been identified in almost all organisms, including humans. Since then, all human chromosomes with the exception of the Y sex chromosome has been shown to contain microRNAs. MicroRNAs act as local post-transcriptional regulators of gene expression, and it has been hypothesized that up to 60% of mRNA transcripts in the body are under microRNA control. MicroRNAs have been identified in almost all cell types, and shown to regulate a wide variety of cellular functions. In particular, numerous miRs have been found in the central nervous system (CNS), some exclusively so, with a list of described functions which continues to expand. Here, I will review the current literature describing microRNAs in the CNS.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Cellular & Molecular Physiology.; Advisor: Michael Forgac.; Committee: Jamie Maguire, and Kathleen Dunlap.; Keywords: Neurosciences, Biochemistry, and Physiology.